Too Early for Foreign Languages! A Critical Review of Young Children’s Internal Readiness for Language Learning: - Fitriyah, Lailatul; Rokhmawan, Tristan; Ramdhani, Reviandy Azhar (Edupedia Publisher, 2025)
This study aims to explore the internal mechanisms, aptitude, intelligence, motivation, and cognitive style that influence second language (L2) acquisition among early childhood learners. Grounded in psycholinguistic and developmental perspectives, this research addresses the lack of contextualized strategies for foreign language instruction at the early childhood education (ECE) level in Indonesia. This qualitative study employed a library research design, using thematic analysis of selected scholarly works from 1959 to 2025. Sources were classified into three thematic clusters: (1) internal processing mechanisms (e.g., phonological memory, LAD function), (2) aptitude and intelligence (e.g., MLAT, linguistic universals), and (3) motivation and cognitive style (e.g., intrinsic-affective-social motivation, field-dependence). Data synthesis was conducted to classify key constructs and pedagogical implications. The results revealed that young learners acquire L2 more effectively through emotionally engaging, context-rich, and multisensory exposure rather than formal grammatical instruction. Children benefit from environments that support referential learning, phonological sensitivity, and social-linguistic modeling. Formal instruction was found to be less effective due to developmental mismatches. A classification model was constructed to visually present the findings. This study offers a comprehensive synthesis that bridges second language acquisition theories with early childhood development. It presents an original classification framework linking cognitive-affective variables with instructional strategies suitable for L2 exposure in early childhood. This research provides critical insights for curriculum developers, early childhood educators, and policymakers aiming to implement developmentally appropriate foreign language instruction. The findings support the need for translanguaging, play-based, and emotionally supportive environments for optimal early language acquisition.